A fast algorithm for the measurement of stimulus-frequency otoacoustic emission suppression tuning curves based on multi-level swept suppressor tones - Xu, Runyi; Liu, Yin; Gong, Qin (Applied acoustics, 2023)
•Based on the swept suppressor tones, we propose a novel fast algorithm for measuring stimulus-frequency otoacoustic emission (SFOAE) suppression tuning curves (STCs) in human ears.•The obtained SFOAE STCs are consistently reproduced in repeated measures and are nearly equivalent to those obtained by the traditional one.•The obtained SFOAE STCs are with more than twice the frequency resolution, while their test time is nearly the half compared with traditional one. Algorithms for measuring stimulus-frequency otoacoustic emission (SFOAE) suppression tuning curves (STCs) typically use pure tones as suppressors, leading to procedures which are time-consuming and difficult to apply in clinical settings. A fast algorithm based on multi-level swept suppressor tones (MLSST) is proposed in this study. Taking advantage of the time-varying frequencies of swept tones, the suppression effects on SFOAE produced by swept suppressor tones are obtained within a single test. Further, a SFOAE STC may be extracted by interpolation from a set of suppression-effect functions at multiple suppressor levels. In the present study, SFOAE STCs were obtained in twenty-six normal-hearing subjects using the fast MLSST and the traditional pure-tone algorithms. SFOAE STCs were measured with high test–retest repeatability using the MLSST algorithm (average mean absolute errors of 2.12 dB) and were nearly consistent with the SFOAE STCs obtained by the pure-tone algorithm (average mean absolute errors of 3.13 dB). In addition, with>1.8 times frequency solution of the acquired curves, the measurement speed of our MLSST algorithm was approximately 2.14 times faster than the traditional one.